MANAGEMENT OF FRACTURE OF MUSCULOSCELETAL TRAUMA - Adi Mahartha, Gde Rastu; Maliawan, Sri; Kawiyana, Ketut Siki (E-Jurnal Medika Udayana; vol 2 no3 (2013):e-jurnal medika udayana, 2013)
Fracture is a loss of continuity of bone, either total or partial, is usually caused by trauma. Overall incidence of fractures was 11.3 in 1,000 per year, in males was 11.67 in 1000 per year, whereas in 10.65 in 1,000 women per year. The classic symptom is a history of trauma fracture, pain and swelling in the broken bones, deformity, musculoskeletal dysfunction, breaking the continuity of the bone, and neurovascular disorders. Principles of fracture treatment is to restore the position of the fracture to its original position (reposition) and held that position during the healing of fractures (immobilization). Special in open fractures, must be considered the danger of infection, either general or local infection.
Keywords: fracture, repositioning, immobilization, infection